Microstructure and mechanical properties of injection moulded Nimonic-90 superalloy parts - (:unkn) unknown (MANEY PUBLISHING, 2012)
This study aims to determine optimum sintering and heat treatment parameters of powder injection moulded Nimonic-90 powder parts. Determination of optimum heat treatment conditions for sintered parts aimed to achieve maximum densities, and the microstructure and mechanical properties of the produced parts were characterised in sintered and heat treated conditions. Injection moulding feedstock was prepared by mixing Nimonic-90 powder with a multicomponent binder system. After moulding, the samples were subjected to a debinding process that consists of solvent and thermal steps. To determine the sintering temperatures, the debinded samples were subjected to differential scanning calorimetry analysis, and then they were sintered at various temperatures under high level vacuum. After sintering, density measurements and optical microscope examinations were performed. The highest density values were determined for the samples that were sintered at 1330 degrees C for 3 h. Different aging treatments were performed on the samples that achieved the highest sintered density, and the microstructures and mechanical properties were then characterised. It was determined that heat treatments had a beneficial effect on the mechanical properties of the material. Though the mechanical properties of the injection moulded materials produced were lower than the wrought Nimonic-90 materials, they have superior mechanical properties compared with cast Nimonic-90 alloys.
Keywords: Powder injection moulding; Superalloy; Nimonic-90; Sintering; Microstructure; NICKEL-BASED SUPERALLOYS; BASE SUPERALLOYS